Clinical and Microbiological Evaluation of Local Doxycycline and Antimicrobial Photodynamic Therapy during Supportive Periodontal Therapy: A Randomized Clinical Trial - Raluca Cosgarea; Sigrun Eick; Ionela Batori-Andronescu; Søren Jepsen; Nicole B. Arweiler; Ralf Rößler; Torsten Conrad; Christoph A. Ramseier; Anton Sculean (Antibiotics, 2021)
The aim of this study was to evaluate the clinical and microbiological effects of subgingival instrumentation (SI) alone or combined with either local drug delivery (LDD) or photodynamic therapy (PDT) in persistent/recurrent pockets in patients enrolled in supportive periodontal therapy (SPT). A total of 105 patients enrolled in SPT were randomly treated as follows: group A (n = 35): SI +PDT and 7 days later 2nd PDT; group B (n = 35): SI+LDD; group C (n = 35): SI (control). Prior intervention, at 3 and 6 months after therapy, probing pocket depths, clinical attachment level, number of treated sites with bleeding on probing (n BOP), full mouth plaque and bleeding scores (gingival bleeding index, %BOP) were recorded. At the same time points, 8 periodontopathogens were quantitatively determined. All three treatments resulted in statistically significant improvements (p < 0.05) of all clinical parameters without statistically significant intergroup differences (p > 0.05). Several bacterial species were reduced in both test groups, with statistically significantly higher reductions for LDD compared to PDT and the control group. In conclusion, the present data indicate that: (a) In periodontal patients enrolled in SPT, treatment of persistent/recurrent pockets with SI alone or combined with either PDT or LDD may lead to comparable clinical improvements and (b) the adjunctive use of LDD appears to provide better microbiological improvements for some periodontal pathogens than SI alone or combined with PDT.